Initial Development of the Activity Card Sort-Advancing Inclusive Participation from a Homeless Population Perspective - Quinn P. Tyminski; Ronald R. Drummond; Claire F. Heisey; Shelby K. Evans; Audra Hendrix; Lisa A. Jaegers; Carolyn M. Baum (Hindawi-Wiley, 2020)
Importance. Nonsanctioned occupations are those deemed socially unacceptable, unhealthy, or illegal, yet they hold meaning for individuals. A gap in occupational therapy evaluation and intervention to address a broader perspective on occupations prompted the adaptation of the Activity Card Sort tool to explore participation in nonsanctioned occupations. Methods. Develop a new version of the Activity Card Sort-Advancing Inclusive Participation to include occupations experienced by the homeless population, including nonsanctioned occupations. This study occurred in two phases: (1) tool development (item selection, content expert review, line development drawing, and assessment of content validity) and (2) tool use to determine face validity. Participants were selected through a convenience sample at a local homeless shelter and academic institution. Participants experiencing homelessness (phase 1: N=13, phase 2: N=10) were required to be seeking services at the homeless shelter, while nonhomeless participants (phase 2: N=30) worked full-time, resided with a significant other, and had personal transportation. Results. An assessment of 76 occupations, corresponding line drawings, and follow-up questions was created. An initial construct validity study demonstrated differences between occupational participation of those who are homeless and nonhomeless in the areas of social engagement, nonsanctioned occupations, work and education, and home management. Both groups reported previous, current, or desired engagement in the occupations identified in the assessment. Conclusions and relevance. The purpose of this study was to create an inclusive assessment for use in the homeless population and complete a construct validity study of the assessment tool. Although the results indicated some differences in the frequency with which occupations were performed, the results demonstrated that all individuals participate in occupations that many not contribute to their health and wellness. This initial work supports the future development of a tool that is inclusive of all occupations to obtain a holistic picture of an individual's participation.